Pengaruh upah minimum, pertumbuhan ekonomi dan investasi terhadap penyerapan tenaga kerja sektor industri di Provinsi Jambi tahun 2000-2018 - Rita Anggraini; Purwaka Hari Prihanto; Muhammad Safri (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2020)
This study aims to: 1) To determine the development of labor absorption in the industrial sector, minimum wages, economic growth, and industrial investment in Jambi Province 2000-2018. 2) To determine the effect of minimum wages, economic growth, and industrial investment on labor absorption in Jambi Province 2000-2018. The research analysis tool uses multiple linear regression analysis tools. Based on the results of the F test, it is known or obtained a probability significance of 0.000 is smaller than alpha 5 percent, namely 0.05. This means that the minimum wage, economic growth, and investment variables together have a significant effect on the labor absorption variable. The variable that has a significant effect on labor absorption in the industrial sector in Jambi Province is the minimum wage variable because the probability value is 0.018 where the probability value is less than 0.05, while the variables of economic growth and industrial investment do not have a significant effect on employment in the sector. industry in Jambi Province because the probability value is greater than 0.05. Keywords: Minimum wages, Economic growth, Investment and Absorption of industrial sector workers